A MULTI-MODAL DISCOURSE ANALYSIS FOCUSED ON WOMEN IN THE "I AM STROKE" PUBLIC SERVICE ANNOUNCEMENTS. (11th November 2018) - Davis, L
Abstract: This multi-modal discourse analysis explored the taken-for-granted notions of woman and stroke. Guided by discourse and feminist post-structural theory we explored how women were discursively portrayed in a series of five, 30-second US Public Service Announcements titled "I Am Stroke". Discourse methodology requires the researcher ask questions of the data to "lift-out" possible meaning potentials beyond a stated purpose. The two women in the series were younger, and portrayed as "sweetly supportive" or "strong and powerful". Since stroke occurs more often in older women and women of color we asked: Why did the creators choose younger instead of elderly women and why were they both white? Were the creators drawing on broader discourses of aging women in society or health in women of color? Would the message or the meaning potentials for viewers change if others were included? The three men included were young, old, black and white.